2015
DOI: 10.7860/jcdr/2015/11741.5756
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial Infection after Cosmetic Procedure with Botulinum Toxin A

Abstract: A 45-year-old woman presented to the dermatology clinic complaining of lesions that had appeared soon after the injections of botulinum toxin A, at the sites of the injections. Gradually the lesions increased in size. The injections had been administered for cosmetic proposes five months before.Physical examination showed erythematous, swollen, warm, and tender plaques and nodules at the points of injection: the procerus muscle zone and the pars externa of the orbicularis oculi muscle [Table/ Fig-1]. One of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…A total of 24 cases across 18 studies of cutaneous NTM infection after cosmetic injections reported from 2013 to 2023 were identified in the search 4–21 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 24 cases across 18 studies of cutaneous NTM infection after cosmetic injections reported from 2013 to 2023 were identified in the search 4–21 …”
Section: Resultsmentioning
confidence: 99%
“…A total of 24 cases across 18 studies of cutaneous NTM infection after cosmetic injections reported from 2013 to 2023 were identified in the search. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The characteristics of the included studies are summarized in Table 1. The majority of the patients were female (23 out of 24 patients), with ages ranging from 28 to 56 years old.…”
Section: Results Of Literature Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Granulome nach BoNT-A-Injektionen treten mit einer großen Spannbreite an klinischer Latenz auf: zwischen zwei Tage und bis zu sechs Jahre nach BoNT-A-Injektion wurden beschrieben, die Diagnose wird oft mittels Biopsie gestellt [ 3 ]. Nur wenige Veröffentlichungen beschreiben purulente Granulome, wobei bei diesen, im Gegensatz zu unserem Fall, Mykobakterien nachgewiesen worden waren [ 4 , 5 ].…”
Section: Diskussionunclassified
“…2 Skin and soft tissue infections caused by NTM have been increasingly described as a complication associated with cosmetic procedures. 3 Cases or outbreaks are therefore reported after mesotherapy, 4 hair transplant, 2 injection of botulinum toxin A, 5,6 illicit intramammary injections of silicone, 7 liposuction, 8 face lift, 9 piercing, 10 and tattooing. 11 However, few cases of secondary NTM infections after injection of hyaluronic acid filler have been reported.…”
Section: Introductionmentioning
confidence: 99%